2021
DOI: 10.3389/fcell.2021.654467
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Imbalance as the Vertex Between Fetal Valproate Syndrome and Chromatinopathies

Abstract: Prenatal exposure to valproate (VPA), an antiepileptic drug, has been associated with fetal valproate spectrum disorders (FVSD), a clinical condition including congenital malformations, developmental delay, intellectual disability as well as autism spectrum disorder, together with a distinctive facial appearance. VPA is a known inhibitor of histone deacetylase which regulates the chromatin state. Interestingly, perturbations of this epigenetic balance are associated with chromatinopathies, a heterogeneous grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 173 publications
(201 reference statements)
0
3
0
Order By: Relevance
“…Lopez-Atalaya et al showed that deficits in the levels of histone H2A and H2B acetylation in lymphoblastoid cell lines derived from two RSTS1-related CREBBP patients were rescued by treatment with TSA [ 175 ]. Furthermore, Parodi et al very recently reviewed the overlap between chromatinopathies and fetal valproate syndrome, highlighting valproic acid as a promising therapeutic approach for RSTS [ 176 ]. However, these results should be confirmed in a therapeutic trial with a large cohort of patients as HDACi represent a therapeutic option for RSTS patients.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Lopez-Atalaya et al showed that deficits in the levels of histone H2A and H2B acetylation in lymphoblastoid cell lines derived from two RSTS1-related CREBBP patients were rescued by treatment with TSA [ 175 ]. Furthermore, Parodi et al very recently reviewed the overlap between chromatinopathies and fetal valproate syndrome, highlighting valproic acid as a promising therapeutic approach for RSTS [ 176 ]. However, these results should be confirmed in a therapeutic trial with a large cohort of patients as HDACi represent a therapeutic option for RSTS patients.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Another study demonstrated that valproate use by mothers had produced offspring who demonstrated a significant reduction in performance at school while comparing children who were not exposed to antiepileptic medication and those whose mothers had reported lamotrigine use [27]. Prenatal antiepileptic medication exposure causes retardation of growth in infants in comparison to neonates who are not exposed to medication [28]. Some of the probable mechanisms responsible for the causation of fetal valproate syndrome disorders include programmed cell death and degeneration of neurons seen in the brain of rats (prenatally exposed to valproic acid) during development and increased plasticity of synapses shown in the medial prefrontal cortex of these rats, and reduction in folic acid levels.…”
Section: Sodium Valproate In Pregnancymentioning
confidence: 99%
“…On the other hand, VPA is an epigenetic agent, a histone deacetylase inhibitor (HDACi) that acetylates histones and thus affects chromatin state and gene expression [ 4 , 5 ]. Indeed, some chromatinopathies, a heterogeneous group of Mendelian disorders, were found to be phenocopies of FVSD [ 6 ], implying the necessity for further research on epigenetic mechanisms such as posttranslational histone modifications during development. In a seven-day in vitro culture of the mouse gastrulating embryo proper, HDACi VPA downregulated and the other HDACi trichostatin A (TSA) upregulated the expression of pluripotency and the three germ-layer-differentiation genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%